Cellular immunotherapy targeting CLL-1 for juvenile myelomonocytic leukemia - Juwita Werner; Alex G. Lee; Chujing Zhang; Sydney Abelson; Sherin Xirenayi; Jose Rivera; Khadija Yousuf; Hanna Shin; Bonell Patiño-Escobar; Stefanie Bachl; Kamal Mandal; Abhilash Barpanda; et al. (Nature Communications)
Abstract Juvenile myelomonocytic leukemia (JMML) is a myeloproliferative disorder that predominantly affects infants and young children. Hematopoietic stem cell transplantation (HSCT) is standard of care, but post-HSCT relapse is common, highlighting the need for innovative therapies. While adoptive immunotherapy with chimeric antigen receptor (CAR) T cells has improved outcomes for patients with advanced lymphoid malignancies, it has not been comprehensively evaluated in JMML. In the present study, we use bulk and single-cell RNA sequencing, mass spectrometry, and flow cytometry to identify overexpression of CLL-1 (encoded by CLEC12A) on the cell surface of cells from patients with JMML. We develop immunotherapy with CLL-1 CAR T cells (CLL1CART) for preclinical testing and report in vitro and in vivo anti-leukemia activity. Notably, CLL1CART reduce the number of leukemic stem cells and serial transplantability in vivo. These preclinical data support the development and clinical investigation of CLL-1-targeting immunotherapy in children with relapsed/refractory JMML.